THE IMPACT OF THE VICTIM MINDSET ON THE FULFILLMENT OF HUSBAND AND WIFE RIGHTS AND OBLIGATIONS (FIKIH MUNAKAHAT PERSPECTIVE) - Muhammad Fadhlan Fauzan; Emha Hasan Amiinulloh Asyari (Program Pascasarjana UIN Sumatera Utara, 2026)
Household conflicts in contemporary Muslim societies are influenced not only by social and economic factors but also by individual psychological patterns, one of which is playing victim. This mindset is characterized by a tendency to perceive oneself as a victim, shift responsibility to one's spouse, and avoid self-reflection in resolving marital conflicts. This study aims to analyze the impact of playing victim on the fulfillment of spousal rights and obligations from the perspective of fiqh munakahat (Islamic family jurisprudence). Employing a qualitative library research approach, the study draws upon classical and contemporary Islamic legal literature as well as works on interpersonal psychology, which are analyzed through content analysis. The findings reveal that playing victim leads to a distortion of responsibility, hinders the fulfillment of spousal rights and obligations, and undermines communication and relational balance within the family. From the perspective of fiqh munakahat, such behavior may contribute to taqsir (negligence in fulfilling obligations) and, if sustained over time, may develop into conditions resembling nusyuz (persistent disregard of marital obligations). The novelty of this study lies in its integration of interpersonal psychological analysis and fiqh munakahat to explain how individual psychological tendencies can influence the implementation of family norms in Islam. These findings highlight the importance of a multidisciplinary approach in fostering marital relationships that are just, responsible, and harmonious.